Complexing reverse transcriptase with polyspermine-ribonuclease. - Bandyopadhyay, A K (1980)
Polyspermine-ribonuclease (Mr approximately 17 000) and the enzyme transcriptase from Rauscher-leukaemia virus (Mr approximately 70 000) form a complex Mr approx. 160 000) such that the molar ratio of polyspermine-ribonuclease to reverse transcriptase is 5:1. The most favourable condition for complex-formation is in a solution consisting of 0.01 M-Tris/HCl buffer, pH 7.5, 0.25 M-KCl and 1 mM-Mn2+ at 37 degrees C. The association of the two enzymes retains full RNAase activity, but reverse-transcriptase activity is completely inhibited when ribonuclease-sensitive polymers such as (dG)12 x (rC)n or viral 70S RNA are used as primer templates.